MANAJEMEN DAN PENILAIAN DIRI PUSTAKAWAN DALAM USAHA MENGEMBANGKAN MINAT BACA BERDASARKAN PENDEKATAN RUSSIAN MATOUSCHKA - Majidah Majidah (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
Communication Management is basically a process of communication activities between individuals in an organization that must be done with rational ways of thinking to achieve the goals set through cooperation with others. In libraries, a librarian can build relationships both inside and outside the library if it can carry out communication and self-assessment management. With the management of librarians communication can carry out organizational communication between individual librarians, supervisors and users. The management of librarian communication and librarian's self-assessment are likened to Russian Matouschka dolls which have 4 layers of dolls, which cause (orientation) the interaction in a library. The process of fostering and developing reading interest in readers is well and effective, if the librarian must first be able to recognize and understand himself in communicating.